2018
DOI: 10.1051/matecconf/201814814001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nylon nanofibers on the dynamic behaviour and the delamination resistance of GFRP composites

Abstract: Abstract. Vibrations are responsible for a considerable number of accidents in aircrafts, bridges and other civil engineering structures. Therefore, there is a need to reduce the vibrations on structures made of composite materials. Delamination is a particularly dangerous failure mode for composite materials because delaminated composites can lose up to 60% of their strength and stiffness and still remain unchanged. One of the methods to suppress vibrations and preventing delamination is to incorporate nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…For example, Ref. [23] reported that the natural frequencies of glass fiber composites showed minuscule changes (less than 4%) due to the inclusion of nylon nanofibers. Similar results were found in [24,25], which reported very small changes in the natural frequencies due to the inclusion of carbon nanofibers and nanotubes, respectively.…”
Section: Effect Of Polycaprolactone Nanofibers On the Natural Frequenmentioning
confidence: 99%
“…For example, Ref. [23] reported that the natural frequencies of glass fiber composites showed minuscule changes (less than 4%) due to the inclusion of nylon nanofibers. Similar results were found in [24,25], which reported very small changes in the natural frequencies due to the inclusion of carbon nanofibers and nanotubes, respectively.…”
Section: Effect Of Polycaprolactone Nanofibers On the Natural Frequenmentioning
confidence: 99%
“…This study is focused on the effect of sand particle size on the mechanical properties of similar gypsum cementation materials from the aspects of gypsum hydration reaction mechanism and physical characteristics of sand particle cementation. Meanwhile, the effect of sand particle size on the mechanical properties of similar materials cemented by gypsum is a complex issue, and there are many other influencing factors, including the typical particle size of the cementite [29], the environmental conditions [30,31], and the sand particle gradation [18,[32][33][34][35]. Furthermore, the specific values of the numerical experiments cannot correspond to the laboratory test results one by one, and only reveal the mechanical behavior of similar gypsum materials in the process of compression.…”
Section: Discussionmentioning
confidence: 99%
“…On the comparison of results for higher modes [7][8][9][10][11][12] , Mode 7 has the lowest percentage error as compared to mode 12 in 0/90/45/90 stacking sequences as shown in Table 2. On contrary to 0/90/45/90, 0/45 and 0/90 sequences showed an increase in percentage error on an increase in modes.…”
Section: Effect Of Stacking Sequencesmentioning
confidence: 99%
“…Delamination is the internal crack and can cause reduction in structural stiffness that leads to reduced natural frequency 10 . Vibration is the major influencing parameter towards the failure of aerospace, marine and civil structural components 11 . Therefor specific measures should be taken to overcome the effect of vibrations in composite structures.…”
Section: Introductionmentioning
confidence: 99%